(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Corrosion and scaling are mutual problems appeared in water distribution systems. The strictness of such problems depends on the quality of the water conveyed and the characteristics of the pipeline material. For solving and minimizing such problems, the probability of corrosivity and scaling of water as well as the factors effecting them should be investigated. Four water stability indices (Langlier Saturation Index (LSI), Ryznar Stability Index (RSI), Pockurius Scaling Index (PSI), and Aggressive Index (AI))were used to investigate the stability of treated water from six selected water treatment plants in Babylon province (Al-Hillah Al-Jadeed, Al-Hillah Al-Kadeem, Al-Taiyara, Al-Hussain, Al-Mahaweel and Al-Hashmia) during 2009-2013. According to LSI the treated water quality of the all stations was oversaturated with CaCO3 during the whole studied period (positive LSI values) with a potential of forming a protective layer from calcium carbonate. RSI, PSI and AI results displayed that the water quality was of moderately corrosive which can be considered not harmful for water distribution systems.